RETRACTED: The Influence Of Product Quality, Celebrity Endorsers And Word Of Mouth On The Decision To Purchase Garnier Sakura White Day Cream In Pejaten Village, Selatan Jakarta - Ratna Farida; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research focuses on assessing the impact of product quality, celebrity endorser, and word of mouth on the purchase decision of Garnier Sakura White Day Cream in Pejaten Village, South Jakarta. The primary data were collected through a questionnaire distributed to 100 respondents who had used Garnier Sakura White Day Cream. The data were analyzed using the multiple linear regression method with SPSS version 22.0. The findings indicate that product quality, celebrity endorser, and word of mouth have a positive and significant influence on the purchase decision of Garnier Sakura White Day Cream in Pejaten Village, South Jakarta. This implies that consumers in this area consider these factors when making decisions about purchasing the mentioned skincare product. The study contributes valuable insights for businesses, highlighting the importance of maintaining product quality, utilizing effective celebrity endorsements, and fostering positive word of mouth to enhance consumer decision-making in the competitive skincare market.